PERAN INTELLECTUAL CAPITAL MEMODERASI PENGARUH CORPORATE GOVERNANCE TERHADAP PROFITABILITAS - Bekti Syahputra (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The problems in the study proved inconsistent with the results of previous studies which indicated a problem in this study. This study uses a quantitative approach which in the opinion of Indriantoro and Supomo (2011), that quantitative research emphasizes theory testing through numerical measurement of research variables and data analysis using statistical procedures. The results of the study showed that there was no significant effect of GCG on profitability. CEE moderated GCG on profitability significantly negatively, HCE moderated GCG on profitability negatively but not significantly. And SCE moderates GCG on profitability significantly negatively. Therefore, these three components need to be handled more seriously considering that the results of the CEE and SCE research are significantly negative, and especially HCE which has no significant effect in order to have a significant positive effect on profitability.